Firm‐Level Evidence for the Language Investment Effect on SME Exporters. (24th February 2015) - Foreman‐Peck, James; Zhou, Peng
Abstract Both analysis of international trade and the knowledge resource theory of the firm imply that language skills should play a vital role in exporting. This may be apparent to large multinationals with sites in many different linguistic locations, but we show it is less obvious to smaller companies. With data on the language used by each of a large sample of European small‐ and medium‐sized enterprises in their export markets, we test and estimate the effects of language assets on language performance in export markets and on export sales. Controlling for the possibility that language skills may be acquired by exporting, we find a very substantial export return to linguistic expertise, indicative of unexploited gains from investment in languages. There is also evidence of greater under‐investment in language skills in English‐speaking Europe.